Best practices in hospitality and tourism marketing and management : A quality of life perspective / Ana María Campón-Cerro, José Manuel Hernández-Mogollón, José Antonio Folgado-Fernández editors - Campón-Cerro, Ana MaríaEditor
This volume analyses the positive effects that tourism generates on resident’s quality of life, and how this influences tourists’ quality of life as they enjoy an enriching experience in the destination they visit. It provides significant theoretical and empirical contributions, as well as, case studies related to quality of life in hospitality and tourism marketing and management. This volume is the result of the effort that many researchers from all over the world have done to spread some new light on this outstanding research line and add knowledge on the relationship between tourism and quality of life of both residents and tourists. This last is highlighted as a fundamental factor to take into account for the development of new tourism practices. This volume is a true reference for researchers, students and professionals working in tourism marketing and management.